A comparative study of serology and PCR for the diagnosis of brucellosis in goats - TRANGADIA, B J; PRASAD, M C; RAMANI, U V; PANDYA, G M; KURKURE, N V (The Indian Journal of Animal Sciences, 2020)
Brucellosis is an economically important infectious disease of livestock causing abortions, infertility, delayed oestrus, interrupted lactation, increased condemnation and loss of milk production besides its zoonotic nature. The present study was conducted to compare serological assays and polymerase chain reaction (PCR) for the diagnosis of caprine brucellosis. A total of 301 whole blood samples to extract DNA for PCR and serology were collected from goats maintained at various organized herds, panjarapoles, slaughter house, local meat markets, etc. in South Gujarat region of India. Out of 301 serum samples tested, 7 samples (2.33%) were positive by all the three serological tests, viz. rose bengal plate test (RBPT), indirect ELISA (iELISA) and immunochromatographic assay (ICA). Among 301 DNA samples, genus specific PCR detected DNA of Brucella spp. in 11 samples by targeting BCSP 31 and IS-711 genes to get 223 bp and 350 bp PCR products on agarose gel electrophoresis. None of the seven serologically positive samples showed Brucella genus-specific DNA amplification by PCR and similarly all PCR positive samples were negative on serology.